Applying a Needs Assessment Model for Improving Agricultural Education in Guinea - Roger Hanagriff; Miraj Wallace; Jack Elliot (Journal of International Agricultural and Extension Education, 2020)
Extension education is considered an essential component of improving agricultural sustainability by diffusing innovations that increase crop yield and alleviate poverty in Guinea, Africa. To accomplish learning outcomes, extension agents must be confidentand competent in their instructional abilities. This is achieved by self-evaluation of their training needs. The objective of this quantitative research was to conduct a needs assessment with leaders of the Farmer-to-Farmer educational programto identifytheir training needs. A purposive sample of thirteen higher-education leaders of the Farmer-to-Farmer program were asked to identify their educational needs and prioritize items contributing to the knowledge gap following their participation in a ten-day training. The Borich Needs Assessment Model was used to calculate the mean weighted discrepancy score (MWDS) of all items. The top five content areas with the greatest reported needs were: Power Point presentations (MWDS = 5.72), teaching financial management (MWDS = 5.51), using SWOT analysis (MWDS = 4.5), teaching marketing concepts (MWDS = 4.36) and incorporating stakeholders (MWDS = 4.35). Following a Pre/Post-Test, the top five content knowledge improvement areas and percent increase in reported knowledge were utilizing strategic planning (176%), using Borich (1970) for program needs assessment (153%), using SWOT analysis (122%), analyzing external influences in educational programs (115%) and strategies to conduct farm trials (67%). Respondents reported increased confidence in seeking stakeholder needs and building resources to increase program value. The results have implications to build education equity and sustainability in Guinea.
Keywords: Borich needs assessment; agriculturalextension education; Guinea agriculture; program planning; strategic planning; Farmer-to-Farmer